2016
DOI: 10.1158/1078-0432.ccr-15-3104
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Circulating CD33+CD11b+HLA-DR− Myeloid Cells in Patients with Stage IV Melanoma Treated with Ipilimumab

Abstract: Purpose: High levels of circulating myeloid-derived suppressor cells (MDSCs) in various cancer types, including melanoma, were shown to correlate with poor survival. We investigated whether frequencies of circulating CD33 þ

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
125
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 173 publications
(138 citation statements)
references
References 43 publications
11
125
0
2
Order By: Relevance
“…Indeed, the role of MDSCs as a biomarker for ipilimumab treatment was demonstrated in a number of studies, mostly reporting correlations between monocytic MDSCs and clinical response. 18,23,24,[29][30][31][32] Kitano and colleagues developed a computational algorithm-based method to perform a uniform analysis of the levels of a monocytic subset in melanoma patients treated with ipilimumab at 3 or 10 mg/kg and found a significant association between levels of Lin…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the role of MDSCs as a biomarker for ipilimumab treatment was demonstrated in a number of studies, mostly reporting correlations between monocytic MDSCs and clinical response. 18,23,24,[29][30][31][32] Kitano and colleagues developed a computational algorithm-based method to perform a uniform analysis of the levels of a monocytic subset in melanoma patients treated with ipilimumab at 3 or 10 mg/kg and found a significant association between levels of Lin…”
Section: Discussionmentioning
confidence: 99%
“…52 Another study reported that circulating CD33 + CD11b + HLA-DR − MDSCs from peripheral blood can be used as biomarkers to predict response and survival of stage IV melanoma patients in ipilimumab treatments. 53 Low levels of MDSCs prior to CTLA-4 therapy correlated with an objective clinical response, long-term survival, and improved clinical status. The presence of more than 55.5% of circulating CD33 + CD11b + out of the HLA-DR − cells in 56 patients was associated with significantly short OS (p < 0.003), a median of 6.5 months, in comparison to the group showing lower MDSC frequencies, with a median survival of 15.6 months.…”
Section: Predictive Markers Of Anti-ctla-4 Therapymentioning
confidence: 93%
“…Thus, in melanoma patients treated with Ipilimumab, decreased amounts and immunosuppressive functionality of both monocytic and polymorphonuclear MDSCs correlated with beneficial therapeutic effects [65,131,135,136,137]. Moreover, non-responding patients showed also elevated serum levels of inflammatory molecules S100A8/A9 and high mobility group box 1 (HMGB1), suggesting that MDSC and chronic inflammatory factors can be not only therapeutic targets in cancer patients but also serve as new biomarkers detecting the group of advanced melanoma patients who may benefit from Ipilimumab therapy [135].…”
Section: Neutralizing Immunosuppression Induced By Mdscsmentioning
confidence: 99%